The Influence of Corporate Governance on Financial Reporting Quality in the Banking Sector - Rusdiah Hasanuddin; Nadya Nurhidayah Nurdin; Nurasia Natsir (International Forum of Researchers and Lecturers, 2025)
This study examines the impact of corporate governance structures on the transparency and accuracy of financial reporting in banking institutions. Using a quantitative research approach, the study analyzes data from 150 banks across 25 countries over a five-year period (2019-2023). Multiple regression analysis reveals that board independence, audit committee effectiveness, and ownership concentration significantly influence financial reporting quality. The findings indicate that stronger corporate governance mechanisms lead to improved financial reporting quality, with board independence having the strongest positive impact. This research contributes to the existing literature by establishing empirical evidence of the relationship between specific corporate governance mechanisms and financial reporting quality in the banking sector, which has implications for regulatory policy and banking governance practices.